THE VALUE RELEVANCE OF ENVIRONMENTAL PERFORMANCE, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, AND RETURN ON EQUITY - Gunardi, Ega Jenny; Widianingsih, Luky Patricia; Ismawati, Anastasia Filiana (Research In Management and Accounting (RIMA), 2021)
This study aims to examine the value relevance of green accounting practice measured by environmental rating through PROPER which is assessed by the Ministry of Environment and Forestry (KLHK) and environmental disclosure activities from an internal party, called sustainability report, of listed mining and agriculture companies on the Indonesian Stock Exchange. This study also tests whether return on equity can strengthen the value relevance of environmental performance and CSR disclosure. The sample consists of 63 firm-year observations. The empirical results showed that the effect of book value of equity and earnings on share price are significant. The study reveals book value of equity exhibits a negative relationship in stock price, while earnings exhibit a negative relationship. However,  environmental performance and CSR disclosure are found not statistically significant impact in terms of share price, which conclude they don’t have value relevance. The study also found that ROE hasn’t succeeded to strengthen the value relevance of environmental performance and CSR disclosure.